Quality Management in Organizing Extracurricular Education at the Bandung Fine Arts High School, Indonesia - Arman Maulana; Rosmayati, Siti; Rahman Tanjung (AGUSPATI Research Institute, 2021)
The purpose of this study was to determine Quality Management in Organizing Extracurricular Education at the Fine Arts High School (Public vocational secondary schools 14 Bandung). The term extracurricular, as an activity to channel interests and talents for students outside school hours. This activity is not just a forum for distributing hobbies. Extracurricular activities can be managed or functioned optimally to become an arena for the formation and development of student character. At school, these extracurricular activities are more of an opportunity to channel students' hobbies. This hobby distribution label often makes activities that are familiarly called by students as extracurricular activities that are managed normally. In fact, with good management, extracurricular activities can have more functions than just a hobby. Extracurricular activities are very effective in shaping character and instilling moral values ​​in students. This extracurricular activity has an important role in developing the character and personality of students. The scope of student competencies developed in extracurricular activities.